PENINGKATAN EMPLOYEE LOYALTY PADA GENERASI MILENIAL DI KABUPATEN GROBOGAN MELALUI VARIABEL FINANCIAL EXTRINSIC REWARD - Adela Eka Ayu Trisiana Adela; Indah Rahayu Indah (LPPM Universitas An Nuur, 2025)
Background: Millennial employees, as a productive age group that currently dominates the workforce, exhibit different characteristics and levels of loyalty compared to previous generations. This demographic shift requires organizations to better understand what drives loyalty among millennials to maintain performance and ensure long-term business sustainability. Purpose: Based on the background and problem formulation, this study aims to describe and analyze the influence of transformational leadership, financial extrinsic reward, and perceived organizational support on employee loyalty among millennial employees in Grobogan Regency. Method: This research uses a quantitative approach. The sample in this study consists of 83 respondents selected through a non-probability sampling method with a purposive sampling technique. Data analysis was conducted using the Partial Least Squares (PLS) statistical technique.. Conclusion: The results indicate that transformational leadership, financial extrinsic reward, and perceived organizational support shows a positive and significant effect on employee loyalty. Suggestion: This study found a gap between the research results and the actual conditions in the field regarding employee loyalty. Therefore, it is suggested that future research be conducted using the same model and topic but with different research objects. In addition, the questionnaire used in this study was still in the form of a closed-ended questionnaire; thus, future research agendas could add open-ended questionnaires to obtain answers with a broader scope.